Hakikat Tafsir Maudhu’i dalam al-Qur’an - Dinni Nazhifah; Fatimah Isyti Karimah (Jurnal Iman dan Spiritualitas, 2021)
This study aims to describe the nature of the interpretation of maudu'i in etymology, terminology and use of the word maudu'i in the Qur'an and the study of interpretation. Research on the interpretation of maudu'i has been carried out by many reviewers of the Qur'an, both in terms of its meaning in language or terms as well as in terms of its application to a particular theme. The research method used in this research is descriptive-analysis and book research. The results of this study are that the word maudu'i is found in the Qur'an 24 times, with one of its meanings being to determine something that is used in a problem or topic. From this, the term maudu'i can be applied to the study of interpretation with the term maudu'i interpretation or in Indonesian known as thematic interpretation. Maudu'i interpretation is a method of interpreting the Qur'an by collecting verses that have the same theme or topic of discussion and also the same purpose and then analyzing them in detail as contained in the rules of tahlili interpretation, explaining their meaning and imposing the laws in it.